Ocular Surface Cooling Corresponds to Tear Film Thinning and Breakup. Issue 9 (September 2015) - Li, Wing; Graham, Andrew D.; Selvin, Steve; Lin, Meng C.
ABSTRACT: Purpose: To investigate the relationship between ocular surface temperature (OST) and tear film thinning and breakup. Methods: Simultaneous imaging of OST and fluorescein tear thinning and breakup (FTBU) was performed on 20 subjects. Subjects were asked to open their eyes and refrain from blinking for as long as they could during testing. Ocular surface temperature was measured using an infrared thermographic camera (FLIR A655sc) and rates of ocular surface cooling (OSC) were analyzed using commercially available software. A method was developed to quantify the rate of FTBU formation using image-processing software. Results: Areas of FTBU and regions of OSC were observed to be colocalized, with localized cooling preceding the formation of FTBU. The rates of OSC and FTBU formation were positively correlated ( r = 0.74). A second-order polynomial model accurately describes the physiological relationship between the area of FTBU and OST (p < 0.001). A linear approximation provides a more clinically interpretable rate of FTBU formation with decreasing OST (p < 0.001), while still retaining high R 2 . Conclusions: The results suggest a direct relationship between FTBU formation and OSC. That cooling of the ocular surface precedes FTBU formation implies a process of evaporation contributing to tear film thinning and breakup. Our study suggests that measuring the OSC rate could be an indirect assessment of tear evaporation and could contribute to the management of evaporative dry eye. Abstract : Supplemental digital content is available in the text.